Study on Image Quality in Teledermatology and Telepathology of Telemedicine Using a Digital Camera - Rai, Krishna Bahadur (Nepal Journal of Multidisciplinary Research, 2021)
Telemedicine is the delivery of health care and exchange of health care information across distance by the use of electronic communication and information technology. Telemedicine (Teledermatology and Telepathology) are being increasing popular and advanced. In ROC curve analysis, it is found that the area under the ROC curve for dermatology is 0.922 saying that a randomly selected individual from the positive group has a test value larger than that for a randomly chosen individual from the negative group by 92% of the time. For histology and cytology, areas under ROC curve are 0.909 and 1.000 respectively. These larger areas indicate high diagnostic accuracy through the high image quality. Again, the P-value for dermatology, histology and cytology are respectively 0.000, 0.000 and 0.001 and all the P-values are low i.e., P < 0.05 which is statistically significant. Therefore, this confirms that an image has good help to detect disease for the doctor’s diagnosis. For detection of disease through images, these images must have good and high quality.